2017
DOI: 10.4172/2165-7556.1000193
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Kinematics Assessment of Bulged Disk Cervical Vertebral

Abstract: Objective: On a cervical disk, the bulge may be produced in the poster lateral direction when there is a combination of lateral bending and compression loading. Although attempts have been made to measure the kinematics of intact vertebral spine but has not been compared with a vertebral spine when the dicks are bulged. The study aims to investigate the effect of a bulged disk on the kinematics of a cervical spine during a flexionextension motion then flexion-extension of five subject patients who had history … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The result obtained in the comparative analyses indicated that the bulged disk intervertebral extension-flexion difference in such subjects is significantly higher than the normal intervertebral difference. The results obtained in the study helped in identification of the technical reasons behind why patients with bulged disks face higher risk of instability during extension-flexion motion as compared with normal subjects [1].…”
Section: Editor Notementioning
confidence: 99%
See 1 more Smart Citation
“…The result obtained in the comparative analyses indicated that the bulged disk intervertebral extension-flexion difference in such subjects is significantly higher than the normal intervertebral difference. The results obtained in the study helped in identification of the technical reasons behind why patients with bulged disks face higher risk of instability during extension-flexion motion as compared with normal subjects [1].…”
Section: Editor Notementioning
confidence: 99%
“…Many attempts have been made to elucidate the kinematics aspect of the functioning of intact vertebral spine; but the study of vertebral spine in the presence of bulged disks is yet to be achieved. The article published by Saveh et al [1] presented the results of a study that investigated the possible changes in the kinematics of cervical spine in the presence of disk bulges. The study specifically highlighted the changes in the flexion extension motion of experimental patients with bulged disks at C5/C6 level.…”
Section: Editor Notementioning
confidence: 99%